Association between dietary factors and colorectal serrated polyps: a systematic review and meta-analysis - Zhu, Zhixin; Guan, Xifei; Liu, Nawen; Zhu, Xiaoxia; Dai, Sheng; Xiong, Dehai; Li, Xiuyang (Frontiers in Nutrition, 2023)
Background: Dietary factors may affect the incidence of colorectal serrated polyps (SP). However, its effects on SP are unclear as epidemiological studies on this topic have showed inconsistent results. The present systematic review and meta-analysis sought to evaluate the effects of dietary factors on SPs. Methods: Studies regarding the association between dietary factors and SPs were identified by searching PubMed, Cochrane library, Embase and Chinese Biomedical Literature database from inception until 27 February 2023. Search terms include serrated, hyperplastic, adenoma, polyps, colorectal, rectal, rectum and risk.Heterogeneity was assessed using I 2 statistics. The meta-analysis was conducted by using a random-effects model, and the pooled effects were expressed with odds ratios (OR) and 95% confidence intervals (95% CI). Probable sources of heterogeneity were identified through meta-regression. Subgroup analysis were based on lesion types, study designs, countries, and so on.Results: 28 studies were ultimately eligible after scanning, and five dietary factors including vitamin D, calcium, folate, fiber and red or processed meat were excerpted.Higher intakes of vitamin D (OR=0.95, 95%CI:0.90-1.02), calcium (OR=0.97, 95%CI: 0.91-1.03) and folate (OR=0.82, 95% CI: 0.6-1.13) were not significantly associated with SP. Fiber intake (OR=0.90, 95% CI: 0.82-0.99) was a protective factor against SPs. Red meat intake increased the risk of SPs by 30% for the highest versus lowest intakes (OR=1.30, 95% CI: 1.13-1.51). For different lesion types, higher folate intake was associated with a decreased risk of HPs (OR=0.59, 95%CI: 0.44-0.79), and higher vitamin D intake decreased the risk of SPs including SSA/P (OR=0.93, 95%CI: 0.88-0.98).Conclusions: Higher dietary fiber intake plays an effective role in preventing SP, while red meat intake is associated with an increased risk of SP. This evidence provides guidance for us to prevent SP from a dietary perspective.